PENGARUH PENERAPAN IAS 39 (TENTANG INSTRUMEN KEUANGAN: PENGAKUAN, DAN PENGUKURAN) TERHADAP MANAJEMEN LABA PADA PERUSAHAAN PERBANKAN: PERBANDINGAN INDONESIA DAN MALAYSIA - Gardina Aulin Nuha (Universitas Muhammadiyah Jember, 2016)
The purpose of this research is to examine the influence of IAS 39 implementation (financial instruments: recognition and measurement) on earning management in banking companies: comparison between Indonesia and Malaysia. This research examine by comparing the earnings management before and after implementing IAS 39. The further examination doing separately between Indonesia and Malaysia. The samples that used in the first examination is 96 firm-years during 2008-2011 which is Indonesia and Malaysia's banking companies. The samples that used in second examination is 71 firm-years during 2008-2011 which is Indonesia's banking companies. For the third examination, the samples that used is 25 firm-years during 2008-2011 which is Malaysia's banking companies. Technique of collecting sample is purposive sampling method. This research using discretionary accruals as an earning management's proxy. Discretionary accruals calculated using Beaver and Engel (1996) method. Data analysis' technique in this research is using differentiate test analysis of independent sample T-test. The result of this research failed to resist H0 for three times examination. This research show that earnings management in banking companies after IAS 39 implementation is bigger than or equal to before it.Keywords: IAS 39, Earnings Management, Dis